Modern preschool education and school readiness in Indonesian cities: A cross-sectional EViews modelling approach - Dahlan, Olivia Putri (Journal of Modern Education Research, 2026)
This article examines modern preschool education in Indonesia by analyzing how developmentally appropriate digital learning, play-based pedagogy, teacher digital pedagogical competence, parental engagement, and learning environment quality relate to school readiness among children aged four to six. This study used a quantitative cross-sectional design with random sampling across several Indonesian cities. The unit of analysis was child-level observation, and the proposed sample consisted of 2,130 observations. Because the data are cross-sectional rather than time-series or panel data, the empirical model is estimated using ordinary least squares in EViews with White robust standard errors. The dependent variable is a school readiness index covering cognitive, socio-emotional, language, self-regulation, and routine-participation indicators. This study contributes to early childhood education management by showing that modernization should not be equated with technology adoption alone. The illustrative EViews results suggest that learning environment quality, teacher competence, parental engagement, and play-based pedagogy are stronger predictors of readiness than digital integration alone. The study concludes that Indonesian PAUD modernization requires balanced investment in teachers, classroom quality, family partnerships, developmentally appropriate play, and carefully governed digital tools.